Performa Dayasaing Komoditas Padi - Benny Rachman (Jurnal Penelitian Pertanian Terapan, 2011)
Change in rice market from controlled market to free market cause domestic rice price is exposed more to market fluctuation. This circumstance directly affects competitiveness of domestic rice farm business. This paper is aimed at assessing competitiveness of rice farm business. The results showed that rice farm business competitiveness was very sensitive to yield decrease, world price of rice, and change in rupiah exchange rate. Strategic attempt to do is to improve efficiency of rice farm business through (a) application of specific technology for specific locations, (b) balance of inputs use, (c) improvement of inputs and output market institution, and (d) farm business management improvement. Keywords : Competitiveness, profitability, institution